Nitric acid uptake in cirrus clouds - Voigt, C.; Schlager, H.; Ziereis, H.; Kärcher, B.; Luo, B. P.; Schiller, C.; Krämer, M.; Popp, P. J.; Irie, H.; Kondo, Y. (Geophysical Research Letters, 2006)
[1] Uptake of nitric acid (HNO3) in Arctic cirrus ice crystals was observed on 11 February 2003 by in-situ instruments onboard the M55 Geophysica aircraft. The cirrus cloud with a mean ice water content of 5.4 mg m(-3) covered northern Scandinavia for several hours and extended up to the thermal tropopause at 12.3 km. Within the cirrus region, on average 9% of the total HNO3 measured as reactive nitrogen (NOy) is present in ice particles, increasing to 19% at temperatures below 205 K. In contrast to previous studies, we discuss the HNO3 uptake in ice in terms of HNO3/H2O molar ratios in ice crystals. The HNO3 content of the ice increases with increasing gas phase HNO3 concentrations and decreasing temperatures. Enhanced uptake of HNO3 in ice and heterogeneous chemistry on cold cirrus clouds may disturb the upper tropospheric ozone budget.